Risk perception among Brazilian individuals with high risk for colorectal cancer and colonoscopy - Santos Erika M; Lourenço Maria TC; Rossi Benedito M (Hereditary Cancer in Clinical Practice, 2011)
Abstract Background Risk perception is considered a motivating factor for adopting preventive behaviors. This study aimed to verify the demographic characteristics and cancer family history that are predictors of risk perception and to verify if risk perception is a predictor of colonoscopy adherence. Methods Individuals with a family colorectal cancer history as indicated by a proband with cancer were interviewed by telephone. They responded to a questionnaire covering demographic characteristics, colonoscopy history and four questions on risk perception. Tests of multiple linear regression and logistic regression were used to identify associations between dependent and independent variables. Results The 117 participants belonged to 62 families and had a mean age of 45.2 years. The majority of these individuals were female (74.4%) and from families who met the Amsterdam Criteria (54.7%). The average risk perception was 47.6%, with a median of 50%. The average population perception of individual risk was 55.4%, with a median of 50%. Variables associated with a higher risk perception were age, gender, religion, school level, income, and death of a family member. The variable predicting colonoscopy was receiving medical information regarding risk (odds ratio OR 8.40). Conclusions We found that family cancer history characteristics (number of relatives with cancer, risk classification) are associated with adequate risk perception. Risk perception does not predict colonoscopy in this sample. The only variable that predicted colonoscopy was receiving medical information recommending screening.